UPAYA MENINGKATKAN KEMAMPUAN KEAKSARAAN AWAL PADA ANAK MELALUI MEDIA KARTU HURUF KELOMPOK B TK NURUL HUDA PEKANBARU TAHUN PELAJARAN 2020/2021 - Nuraini, Seprina (Jurnal Analisis Pendidikan Sosial, 2024)
Aim of this research is to descript the activity of teacher and children in using alphabet card media and to descript the use of alphabet card media in improving the ability of knowing alphabet on 5-6 years children at TK Nurul Huda. This research uses class action research divided into two cycles, each cycle consists of two meetings and each meeting is divided into four stages that is planning, implementing, observing, and reflecting. Then continued with data analysis using descriptive statistic that is cycle based reflection analysis. It means there is improvement in the ability of knowing alphabet through alphabet card media, so this class action research can be stated as success because it has reached the determined success level.